The Challenging Integration Paths of Migrant Health Professionals: The Case of Filipino and Indian Nurses in the UK - Calenda, Davide; Bellini, Andrea (Professions and Professionalism, 2021)
This article examines the role of institutional factors in shaping the integration paths of migrant health professionals. For this purpose, it draws on two studies focusing on Filipino and Indian nurses working in the UK, which rely on quantitative and qualitative methods, including a web survey and semi-structured interviews. The analysis shows that inequalities have arisen from differentiation processes induced by changes in the institutional settings. Furthermore, inequalities are often reflected in poor working conditions. The authors have identified restrictive rules on immigration and access to the profession as a source of uncertainty and reveal the differentiation of entry paths, with those arriving through an international recruitment agency more frequently disappointed with their working conditions.